Do bone geometric properties of the proximal femoral diaphysis reflect loading history, muscle properties, or body dimensions?. Issue 4 (19th April 2019) - Niinimäki, Sirpa; Narra, Nathaniel; Härkönen, Laura; Abe, Shinya; Nikander, Riku; Hyttinen, Jari; Knüsel, Christopher J.; Sievänen, Harri
Abstract: Objectives: The aim of this study was to investigate activity‐induced effects from bone geometric properties of the proximal femur in athletic vs nonathletic healthy females by statistically controlling for variation in body size, lower limb isometric, and dynamic muscle strength, and cross‐sectional area of Musculus gluteus maximus . Methods: The material consists of hip and proximal thigh magnetic resonance images of Finnish female athletes (N = 91) engaged in either high jump, triple jump, soccer, squash, powerlifting, endurance running or swimming, and a group of physically active nonathletic women (N = 20). Cross‐sectional bone geometric properties were calculated for the lesser trochanter, sub‐trochanter, and mid‐shaft of the femur regions. Bone geometric properties were analyzed using a general linear model that included body size, muscle size, and muscle strength as covariates. Results: Body size and isometric muscle strength were positively associated with bone geometric properties at all three cross‐sectional levels of the femur, while muscle size was positively associated with bone properties only at the femur mid‐shaft. When athletes were compared to nonathletic females, triple jump, soccer, and squash resulted in greater values in all studied cross‐sections; high jump and endurance running resulted in greater values at the femoral mid‐shaft cross‐section; and swimming resulted in lower values at sub‐trochanter and femur mid‐shaft cross‐sections. Conclusions: Activity effects from ground impact loading were associated with higher bone geometric values, especially at the femur mid‐shaft, but also at lesser and sub‐trochanter cross‐sections. Bone geometric properties along the femur can be used to assess the mechanical stimuli experienced, where ground impact loading seems to be more important than muscle loading.